Management of Pancreatic Cancer (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This reprint includes a variety of original studies and reviews addressing the diagnosis and management of pancreatic cancer, a highly lethal disease that still has poor prognosis and limited curative-intent therapeutic resources. This reprint also includes studies addressing potential predictors of pancreatic cancer development.